Determinants of student investment decisions: Examining risk perception, educational information, and financial goals with perspectives from Islamic finance - Ismawanto, Totok; Sari, Dessy Handa; Khairiyah, Nurul Musfirah; Arazy, Dito Rozaqi; Opu, Nur Vita; Ramli, Ramli (Journal of Islamic Economics Lariba, 2026)
IntroductionThe rapid expansion of capital market participation among students in emerging economies has increased the importance of understanding the determinants of investment decision-making. Despite growing access to financial information, many student investors still exhibit varying levels of financial literacy, risk perception, and goal orientation. Previous studies suggest that these factors influence investment behavior, yet their combined effects remain insufficiently explored, particularly within student populations and in relation to ethical considerations in Islamic finance.ObjectivesThis study aims to examine the influence of risk perception, educational information, and financial goals on investment decisions among student investors. It seeks to identify which factors significantly shape decision-making behavior and to provide a more comprehensive understanding of investment behavior by integrating cognitive and motivational variables within a unified framework.MethodThe study employs a quantitative approach using a structured questionnaire distributed to 35 members of a capital market study group at a state polytechnic. Data were analyzed using Partial Least Squares Structural Equation Modeling to assess both measurement validity and structural relationships among variables. This method enables the evaluation of complex relationships within a relatively small sample size.ResultsThe findings indicate that educational information and financial goals have a positive and statistically significant influence on investment decisions, while risk perception does not show a significant effect. The model explains a substantial proportion of variance in investment decisions, highlighting the dominant role of knowledge and goal orientation in shaping behavior among student investors.ImplicationsThese results suggest that improving financial literacy and promoting goal-based financial planning are essential for enhancing investment decision quality. The findings also indicate that risk perception may function as a secondary or conditional factor rather than a primary determinant, particularly among less experienced investors.Originality/NoveltyThis study contributes to the literature by integrating risk perception, educational information, and financial goals within a single empirical model and by incorporating an Islamic finance perspective to enrich the interpretation of investment behavior.